1998
DOI: 10.1046/j.1471-4159.1998.71062278.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Mitogen‐Activated Protein Kinase in Phospholipase D Activation Induced by H2O2, but Not by Carbachol, in Rat Pheochromocytoma PC12 Cells

Abstract: Abstract:We have previously reported that hydrogen peroxide (H202) induced a considerable increase of phospholipase D (PLD) activity and phosphorylation of mitogen-activated protein (MAP) kinase in P012 cells. H202-induced PLD activation and MAP kinase phosphorylation were dose-dependently inhibited by a specific MAP kinase kinase inhibitor, PD 098059. In contrast, carbacholmediated PLD activation was not inhibited by the PD 098059 pretreatment whereas MAP kinase phosphorylation was prevented. These findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
(62 reference statements)
1
15
1
Order By: Relevance
“…Since oxidative stress caused by hydrogen peroxide activates p38 MAPK and SAPK/JNK (56 -58), ␣-synuclein might block this reaction and disrupt equilibration of the MAPK pathway, thereby causing cell death. ␣-and ␤-synuclein are known to inhibit phospholipase D activity in vitro (59), which is intimately related to ERK1/2 function (60,61). Considering this along with our own results, ␣-synuclein might bind to a number of molecules in order to regulate signal transduction.…”
Section: ␣-Synuclein Affects Mapk Pathwaysupporting
confidence: 54%
“…Since oxidative stress caused by hydrogen peroxide activates p38 MAPK and SAPK/JNK (56 -58), ␣-synuclein might block this reaction and disrupt equilibration of the MAPK pathway, thereby causing cell death. ␣-and ␤-synuclein are known to inhibit phospholipase D activity in vitro (59), which is intimately related to ERK1/2 function (60,61). Considering this along with our own results, ␣-synuclein might bind to a number of molecules in order to regulate signal transduction.…”
Section: ␣-Synuclein Affects Mapk Pathwaysupporting
confidence: 54%
“…Ito et al. (1998) reported that ERK was involved in PLD activation induced by H 2 O 2 , whereas Rizzo et al (1999) reported that PLD is the upstream signal protein in the activation of the ERK pathway. We investigated whether ERK is the upstream signal protein or downstream target of PLD.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were separated as described for Western blot analysis. (14,15,17). These observations lead us to assume that tyrosine phosphorylation of PLD2 expressed in this cell may regulate its activity.…”
Section: Methodsmentioning
confidence: 96%
“…A number of studies have demonstrated that hydrogen peroxide (H 2 O 2 ) stimulates phospholipase D (PLD), 1 which generates phosphatidic acid (PA), a second messenger in various types of cell, such as endothelial cells (10,11), fibroblasts (12,13), PC12 cells (14 -17), vascular smooth muscle cells (18), and leukemia L1210 cells (19). As the mechanisms underlying the oxidant-induced PLD activation, various factors including protein-tyrosine kinase (10,11,13,14), protein kinase C (PKC) (13,16,19), and mitogen-activated protein kinase (15,17) have been proposed. Direct or indirect tyrosine phosphorylation has been thought to be involved in PLD activation in response to H 2 O 2 exposure.…”
mentioning
confidence: 99%